PEMBUATAN VIRGIN COCONUT OIL (VCO) DENGAN METODE SENTRIFUGASI - Hapsari, Nur; Welasih, Tjatoer (UPN VETERAN JAWA TIMUR, 2010)
Virgin Coconut Oil (VCO) is the oil produced from fresh coconuts. Unlike the ordinary coconut oil, Virgin Coconut Oil (VCO) is produced not by the addition of chemicals or processes that use high heat. Virgin Coconut Oil (VCO) beneficial to health, this is because Virgin Coconut Oil (VCO) contains many medium chain fatty acids (Medium Chain Fatty Acid / MCFA). MCFA are most in the Virgin Coconut Oil (VCO) is Lauric acid (Lauric Acid). Properties that is easily absorbed MCFA will increase metabolism. The addition of energy produced by the metabolism of this produces stimulating effects in the human body thereby increasing the level of energy produced. Core processes in the manufacture of Virgin Coconut Oil (VCO) is located on the separation of oil from water and protein. Many obstacles must be faced for separating oil from water and proteins, such as in the fermentation process, the separation process takes a long time to get the Virgin Coconut Oil (VCO). While the centrifugation, the separation is done by utilizing the weight of the lighter oil. Although I do not require centrifugation long time but the way it has in the purity of the product constraints. This research was conducted by using coconut cream from coconut milk is silenced for 3 hours. Then the cream is incorporated into the instrument with speed centrifuges spin 600,700,800,900 and 1000 rpm with vaiasion times very; 30, 45, 60.75 and 90 minutes after that coconut cream layer divided into 3 layers of oil that is, the middle layer of protein (blondo) and next underwater layer silenced for 8,10,12,14, and 16 hours . The results of virgin coconut oil (VCO) is obtained and then analyzed with the parameters water content, protein content, Lauric acid, color and odor. From the research, obtained the best conditions of rotational speed centrifuges at 1000 rpm and centrifuges turnaround time 90 minutes and 8 hours stagnand time with the quality of Virgin Coconut Oil (VCO) which produced yield: Lauric acid yield of 36.67% and 52.23% results.Keywords: sentrifuge, coconut cream,,% yield results, VCO